Russia between Developing Countries in Europe and Asia - Valery V. SMIRNOV; Vladislav L. SEMENOV; Olga O. KOLOSOVA; Anna N. ZAKHAROVA; Marina M. MITYUGINA; Tamara V. TALANOVA; Nikolay A. EFREMOV (Communications of International Proceedings, 2020)
Research background: Financial and economic status of Russia between developing countries in Europe and Asia. Purpose of the article: Determine the financial and economic role and development opportunities of Russia as a border between developing countries in Europe and Asia. Methods: The research is based on a systematic approach using methods of descriptive statistics and cluster analysis. Findings & Value added: The article describes the need to determine the conditions      and opportunities for the financial and economic development of modern Russia, taking into account the economic and geographical location and international economic cooperation. The development of Russia is considered not only as a criterion, but also as a category for countries that are borders between different socio-economic formations. The study revealed the overall dominant indicator-the GDP deflator, which reflects the activity and instability of the price index. Developing countries have consistently low values relative to Russia, and the Russian GDP deflator is the limit. Asia, with a less capital-intensive economy of the countries, is more stable in the growth rate of the corresponding indicator. Russia has been identified as a source of price index instability and a marginal benchmark for developing countries in Europe and Asia. The main causes of instability are public administration and GDP. As a result of the study, significant groups of instability between Russia and the countries of Asia and Europe were identified. The success of Russia's development as a border between developing countries in Europe and Asia is determined by the correspondence between the limits of economic relations and the existing structure of the Russian economy. This correspondence is the current financial and economic situation of Russia, defined as its status and opportunities for successful development.
Keywords: Border; Instability; Development Limit; Growth Rate.